Signaling and structures underpinning conducted vasodilation in human and porcine intramyocardial coronary arteries - Dora, Kim A.; Lin, JinHeng; Borysova, Lyudmyla; Beleznai, Timea; Taggart, Michael; Ascione, Raimondo; Garland, Christopher (Frontiers in Cardiovascular Medicine, 2022)
Background: Adequate blood flow into coronary micro-arteries is essential for myocardial function. Here we assess the mechanisms responsible for amplifying blood flow into myogenically-contracting human and porcine intramyocardial micro-arteries ex vivo using endothelium-dependent and -independent vasodilators. Methods: Human and porcine atrial and ventricular small intramyocardial coronary arteries (IMCAs) were studied with pressure myography and imaged using confocal microscopy and serial section/3-D reconstruction EM. Results: 3D rendered ultrastructure images of human right atrial (RA-IMCAs) revealed extensive homo and hetero-cellular contacts, including to longitudinally-arranged smooth muscle cells (l-SMCs) found between the endothelium (ECs) and radially-arranged medial SMCs (r-SMCs). Local and conducted vasodilatation followed focal application of bradykinin in both human and porcine RA-IMCAs, and relied on hyperpolarization of SMCs, but not nitric oxide. Bradykinin initiated asynchronous oscillations in endothelial cell Ca2+ in pressurized RA-IMCAs and, as previously shown in human RA-IMCAs, hyperpolarized porcine arteries. Immunolabelling showed small- and intermediate-conductance Ca2+-activated K+ channels (KCa) present in the endothelium of both species and concentration-dependent vasodilation to bradykinin followed activation of these KCa channels. Extensive electrical coupling was demonstrated between r-SMCs and l-SMCs, providing an additional pathway to facilitate the well-established myoendothelial coupling. Conducted dilation was still evident in a human RA-IMCAs with poor myogenic tone, and heterocellular contacts were visible in the 3D reconstructed artery. Hyperpolarization and conducted vasodilation was also observed to adenosine which, in contrast to bradykinin, was sensitive to combined block of ATP-sensitive (KATP) and inwardly rectifying (KIR) K+ channels. Conclusions: These data extend our understanding of the mechanisms that coordinate human coronary microvascular blood flow and the mechanistic overlap with porcine IMCAs. The unusual presence of l-SMCs provides an additional pathway for rapid intercellular signalling between cells of the coronary artery wall. Local and conducted vasodilation follow hyperpolarization of the ECs or SMCs, and contact-coupling between l-SMCs and r-SMCs likely facilitates this vasodilation.